Analysis of Capital Structure Dividend Policy on Shariah Indexed in Indonesia - Annisha Diva Nurizzah Sadiq; Agis Muksin; Siska Rahmayanti; Dadang Husen Sobana (GoResearch - Research & Publishing House, 2024)
This research analyzes the level of influence Debt to Equity Ratio (DER) and Dividend Payout Ratio (DPR) against Price to Book Value (PBV) at PT. Elnusa Tbk during the 2012-2022 period. The aim of this research is to determine the extent to which capital structure and dividend policy influence the market value of companies, especially companies that operate according to sharia principles listed on the Jakarta Islamic Index. Through multiple linear regression analysis, the research results show that DER and DPR do not have a significant effect on PBV, either individually or simultaneously. These two variables contribute 14.4% to PBV, which shows that other factors have a more dominant influence in determining the company's PBV value. These findings show that decisions related to capital structure and dividends at PT. Elnusa Tbk does not directly influence the company's market value, so other factors need to be considered in the company's financial strategy.